TRANSLATION PROCEDURE OF BALINESE CULTURE TERMS INTO ENGLISH IN LEAK HORROR MOVIE BY DREADTEAM - Wartha Dewi, Anak Agung Ratih (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 1 (2024): MaretDO - 10.24843/ling.2024.v31.i01.p08, 2024)
ABSTRACT This study is entitled Translation Procedure of Balinese Culture Terms into English in Leak Horror Movie by Dreadteam. It aims at identifying the types of cultural terms and analyzing the translation procedure applied in the translation of Balinese cultural terms into English in Short Horror. The data were taken from short movie entitled Leak Horror Movie by Dreadteam. The data were collected from the movie by watching the movie and reading the subtitles. This study uses descriptive qualitative method. This study uses Translation Procedure by Vinay and Darbelnet and culture word by Newmark theories. The results show that there are three types of procedure which are fourteen types of borrowing, one equivalent, and two adaptation procedure are found in the short movie that classified in to cultural term there are one social culture, eight social organization and religious, five ecologies, three material cultures and two gesture and habit cultures. All the data have procedure type and their culture categorize which mean the translator tried to conveyed the meaning of the cultural term from the source language to target language. Borrowing type of translation procedure is the most frequent one found in the analysis. That is fifteen out of twenty data .   Keywords: culture word, translation procedure, Balinese culture terms, translation